SWOT Analysis of the Air Transport Fleet in the Hungarian Defence Forces - Boldizsár, Adrienn; Kővári, Botond (Periodica Polytechnica Transportation Engineering, 2020)
Nowadays it is almost unthinkable, that the forces of the army can not deliver the resuply to the troops by air, especially for large distances. This can not be solved by sea or inland transportation, or if it does, it will take unnecessary time or less security. Although the Hungarian Defense Forces have their own transportation fleet, the fleet reserved for this purpose is currently very modest, and there are several reasons why it should be expanded. Developing an own airline fleet is currently a very topical issue. Previously operated Antonov 26 aircraft have little ability to perform the tasks, or in many cases cannot. The two Airbus A319 aircraft purchased in February and Falcon type aircraft purchased in August, although improves the situation, they still do not fill the gap, there are a number of deficiencies in this area. For this I did a SWOT analysis, and with its help we can define the opportunities and threats of development of domestic military air transport.